2019
DOI: 10.1002/cpmb.89
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Transcriptional Activation in Plants Using a Potent Dead Cas9–Derived Synthetic Gene Activator

Abstract: Genetic tools for specific perturbation of endogenous gene expression are highly desirable for interrogation of plant gene functions and improvement of crop traits. Synthetic transcriptional activators derived from the CRISPR/Cas9 system are emerging as powerful new tools for activating the endogenous expression of genes of interest in plants. These synthetic constructs, generated by tethering transcriptional activation domains to a nuclease‐dead Cas9 (dCas9), can be directed to the promoters of endogenous tar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 52 publications
0
9
0
Order By: Relevance
“…Our work suggests that the most effective target regions are within the 350 bp upstream of the TSS. Traditionally, gRNAs for dCas9-TV-based transcriptional activation are first optimized using plant protoplast systems (Li et al 2019b). Our findings that regions 350 bp upstream of the TSS are most effective for dCas9-TV-based transcriptional activation indicate that it can be productive by focusing on the small region without using the protoplast systems.…”
mentioning
confidence: 85%
“…Our work suggests that the most effective target regions are within the 350 bp upstream of the TSS. Traditionally, gRNAs for dCas9-TV-based transcriptional activation are first optimized using plant protoplast systems (Li et al 2019b). Our findings that regions 350 bp upstream of the TSS are most effective for dCas9-TV-based transcriptional activation indicate that it can be productive by focusing on the small region without using the protoplast systems.…”
mentioning
confidence: 85%
“…This synthetic construct that is generated by tethering transcriptional activation domains to a dCas9 can be directed to the promoters of endogenous target genes by single guide RNAs (sgRNAs) to activate transcription. It can also be used to target various effector domains can be fused to dCas9 to enable programmable transcriptional and epigenetic control (Li et al, 2019).…”
Section: Cas 9 Systemmentioning
confidence: 99%
“…A number of researchers have utilized CRISPR systems to investigate the genetic targets behind differentiation blockages commonly seen in causing the development of AML. For instance, Wang et al, identified RNA-binding protein ZFP36L2 as a crucial mechanistic regulator of cell differentiation in AML using cell surface antigen-guided-CRISPR systems (Li et al, 2019;Wang et al, 2021a). Genetic suppression of ZFP36L2 enables myeloid leukemic cells to transit out from an undifferentiated state and resume cellular differentiations.…”
Section: Application Of Various Crispr System In Studying the Functional Genomics Of Amlmentioning
confidence: 99%
“…Controlling gene expression has long been a goal of plant scientists for deciphering plant gene function and improving crop traits. CRISPR-mediated gene regulation, designed by engineering a nuclease-inactivated Cas9 (dCas9) protein with a transcriptional activation domain (VP64) or repressor domains (SRDX), has been very powerful in activating or repressing the endogenous expression of plant genes of interest (Lowder et al, 2017;Li Z. et al, 2019;Malzahn et al, 2019). With the help of gRNA, the dCas9 fusion protein can specifically bind to the promoter region and manipulate the expression of downstream genes.…”
Section: Transcriptional Regulationmentioning
confidence: 99%